MILLIMETER AND SUB-MILLIMETER-WAVE SPECTRUM OF SELENIUM DIOXIDE, SeO2 - Alekseev, E. A.; Baskakov, O. I.; Dyubko, S. P. (Видавничий дім «Академперіодика», 2025)
Subject and Purpose. The work is aimed at investigating the spectra of the ground-state and a few of the excited vibrational states for the main isotopologues of the selenium dioxide molecule, SeO2, in order to provide a reliable basis for its further search in the interstellar medium.Method and methodology. The method is based on real-life measurements and onward analysis of the microwave rotational spectrum of the SeO2 molecule. The measurements are carried out with an automated millimeter wave spectrometer of the Institute of Radio Astronomy of the NAS of Ukraine, (Kharkiv, Ukraine), and the submillimeter-wave spectrometer of the V. N. Karazin Kharkiv National University (Kharkiv, Ukraine).Results. The measurements were carried out within a range between 70GHz and 500 GHz, where frequencies of about 650 rotational transitions were measured. Most of these belong to the 76SeO2 , 77SeO2 , 78SeO2 , 80SeO2 , and 82SeO2 molecules in their respective vibrational ground states. The rest of the lines can be assigned to isotopic species of the 76SeO2 , 77SeO2 , 78SeO2 , 80SeO2 , and 82SeO2 molecules in their excited vibrational state ν2 = 1, while in the case of 80SeO2 in the excited state ν2 = 2 as well. In addition, tentative assignments have been suggested for 10 transitions in the ground -state isotopic species of 77SeO2.Conclusions. The transitions between states characterized by quantum numbers J up to 70 and quantum numbers Kɑ up to 19, embracing the ground-state and first-, and second-order excited vibrational states of the 74SeO2 , 76SeO2 , 77SeO2 , 78SeO2 , 80SeO2 , and 82SeO2 molecules have been identified. Based on these assigned transitions, significantly improved estimates have been obtained for sets of rotational and centrifugal distortion constants, including octic ones, as well as for A-reduced Watson’s Hamiltonian in the Ir coordinate representation. The parameter sets obtained provide for reliable predictions for possible future astronomical search of the most abundant isotopic species of the SeO2 molecule.Key words: selenium dioxide molecule; millimeter wave spectrum; asymmetric top; isotopic substitutionManuscript submitted 29.01.2025Radio phys. radio astron. 2025, 30(2): 141-158REFERENCES1. Messer, J.K., De Lucia, F.C., Helminger, P., 1984. Submillimeter spectroscopy of the major isotopes of water. J. Mol. Spectrosc., 105(1), pp. 139–155. DOI: https://doi.org/10.1016/0022-2852(84)90109-72. Bernath, P.F., 2002 The spectroscopy of water vapour: Experiment, theory and applications. Phys. Chem. Chem. Phys., 4(9), pp. 1501–1509. DOI: https://doi.org/10.1039/b200372d3. Toureille, M., Koroleva, A.O., Mikhailenko, S.N., Pirali, O., Campargue, A., 2022. Water vapor absorption spectroscopy and validation tests of databases in the far-infrared (50–720 cm–1). Part 1: Natural water. J. Quant. Spectrosc. Radiat. Transf., 291, Id. 108326.  DOI: https://doi.org/10.1016/j.jqsrt.2022.1083264. Karlovets, E.V., Mikhailenko, S.N., Koroleva, A.O., Campargue, A., 2024. Water vapor absorption spectroscopy and validation tests of databases in the far-infrared (50–720 cm–1). Part 2: H217O and HD17O. J. Quant. Spectrosc. Radiat. Transf., 314, Id. 108829. DOI: https://doi.org/10.1016/j.jqsrt.2023.1088295. Jørgensen, U.G., Jensen, P., Sørensen, G.O., Aringer, B., 2001. H2O in stellar atmospheres, Astron. Astrophys., 372(1), pp. 249–259. DOI: https://doi.org/10.1051/0004-6361:200102856. Aringer, B., Kerschbaum, F., Jørgensen, U.G., 2002. H2O in stellar atmospheres. II. ISO spectra of cool red giants and hydrostatic models. Astron. Astrophys., 395(3), pp. 915–927. DOI: https://doi.org/10.1051/0004-6361:200213137. Sandor, B. J., Clancy, R. T., 2005. Water vapor variations in the Venus mesosphere from microwave spectra. Icarus., 177(1), pp. 129–143. DOI: https://doi.org/10.1016/j.icarus.2005.03.0208. Pickett, H.M., Cohen, E.A., Margolis, J.S., 1985. The infrared and microwave spectra of ozone for the (0, 0, 0), (1, 0, 0), and (0, 0, 1) States. J. Mol. Spectrosc., 110(2), pp. 186–214. DOI: https://doi.org/10.1016/0022-2852(85)90290-59. Ivanov, S.V., Panchenko, V.Ya., 1994. Infrared and microwave spectroscopy of ozone: historical aspects. Phys.-Usp., 37(7), pp. 677–695. DOI: https://doi.org/10.1070/PU1994v037n07ABEH00003410. Medvedev, I., Winnewisser, M., De Lucia, F. C., Herbst, E., Białkowska-Jaworska, E., Pszczółkowski, L., Kisiel, Z., 2004. The millimeter- and submillimeter-wave spectrum of the trans–gauche conformer of diethyl ether. J. Mol. Spectrosc., 41(2), pp. 333–380. DOI: https://doi.org/10.1016/j.jms.2004.06.01111. Alekseev, E.A., Dyubko, S.F., Ilyushin, V.V., Podnos, S.V., 1996. The high-precision millimeter-wave spectrum of 32SO2, 32SO2 (ν2), and 34SO2 . J. Mol. Spectrosc., 176(2), pp. 316–320. DOI: https://doi.org/10.1006/jmsp.1996.009212. Lovas, F.J., 1985. Microwave spectra of molecules of astrophysical interest. XXII. Sulfur dioxide (SO2). J. Phys. Chem. Ref. Data, 14, pp. 395–488. DOI: https://doi.org/10.1063/1.55572913. Carlotti, M., Dilonardo, G., Fusina, L., Carli, B., Mencarazlia, F., 1984. The submillimeter-wave spectrum and spectroscopic constants of SO2 in the ground state. J. Mol. Spectrosc., 106(1), pp. 235–244. DOI: https://doi.org/10.1016/0022-2852(84)90096-114. Helminger, P.A., De Lucia, F.C., 1985. The submillimeter wave spectrum of 32S16O2, 32S16O2(ν2), and 34S16O2. J. Mol. Spectrosc., 111(1), pp. 66–72. DOI: https://doi.org/10.1016/0022-2852(85)90069-415. Lafferty, W.J., Fraser, G.T., Pine, A.S., Flaud, J.-M., Camy-Peyret, C., Dana, V., Mandin, J.-Y., Barbe, A., Plateaux, J.J., Bouazza, S., 1992. The 3ν3 band of 32S16O2: Line positions and intensities. J. Mol. Spectrosc., 154(1), pp. 51–60. DOI: https://doi.org/10.1016/0022-2852(92)90028-M16. Maki, A.G., Kuritsyn, Yu.A., 1990. High-resolution measurements of the ν2 and 2ν2–ν2 bands of 34S16O2 . J. Mol. Spectrosc., 144(1), pp. 242–243. DOI: https://doi.org/10.1016/0022-2852(90)90319-L17. Belov, S.P., Tretyakov, M.Y., Kozin, I.N., Klisch, E., Winnerwisser, G., Lafferty, W.J., Flaud, J.-M., 1998. High frequency transitions in the rotational spectrum of SO2 . J. Mol. Spectrosc., 191(1), pp. 17–27. DOI: https://doi.org/10.1006/jmsp.1998.757618. Alderson, L., Wakeford, H.R., Alam, M.K., et al., 2023. Early release science of the exoplanet WASP-39b with JWST NIRSpec G395H. Nature, 614, pp. 664–669. DOI: https://doi.org/10.1038/s41586-022-05591-319. Powell, D., Feinstein, A.D., Lee, E.K.H. et al., 2024. Sulfur dioxide in the mid-infrared transmission spectrum of WASP-39b. Nature, 626, pp. 979–983. DOI: https://doi.org/10.1038/s41586-024-07040-920. Safety data sheet: selenium dioxide. Available from: https://www.integraclear.com/msds/S138_26294_101.pdf21. Gottlieb, C.A., Ball, J., 1973. Interstellar sulfur monoxide. Astrophys. J., 184, pp. L59–L64. DOI: https://doi.org/10.1086/18128822. Snyder, L.E., Hollis, J.M., Ulich, B.L., Lovas, F.J., Johnson, D.R., Buhl, D., 1975. Radio detection of interstellar sulfur dioxide. Astrophys. J., 198, pp. L81–L84. DOI: https://doi.org/10.1086/18181723. Abundance in the Universe of the elements. Available from: https://periodictable.com/Properties/A/UniverseAbundance.v.log.html>24. Suess, H.E., Urey, H.C., 1956. Abundances of the elements. Rev. Mod. Phys., 28(1), pp. 53–74. DOI: https://doi.org/10.1103/RevModPhys.28.5325. Anders, E., Ebihara, M., 1982. Solar-system abundances of the elements. Geochim. Cosmochim. Acta, 46(11), pp. 2363–2380. DOI: https://doi.org/10.1016/0016-7037(82)90208-326. Kamiński, T., Gottlieb, C.A., Menten, K.M., Patel, N.A. Young, K.H., Brünken, S., Müller, H.S.P., Mccarthy, M.C., Winters, J.M., Decin, L., 2013. Pure rotational spectra of TiO and TiO2 in VY Canis Majoris. Astron. Astrophys., 551, Id. A113. DOI: https://doi.org/10.1051/0004-6361/20122029027. Takeo, H., Hirota, E., Morino, Y., 1970. Equilibrium structure and potential function of selenium dioxide by microwave spectroscopy. J. Mol. Spectrosc., 34(3), pp. 370–382. DOI: https://doi.org/10.1016/0022-2852(70)90020-228. Takeo, H., Hirota, E., Morino, Y., 1972. Third-order potential constants and dipole moment of SeO2by microwave spectroscopy. J. Mol. Spectrosc., 41(2), pp. 420–422. DOI: https://doi.org/10.1016/0022-2852(72)90216-029. Alekseev, E.A., Baskakov, O.I., Dyubko, S.F., Polevoi, B.I., 1986. Submillimeter rotational spectrum of the 80SeO2 molecule. Opt. Spektrosk., 60(1), pp. 30–32.30. Alekseev, E.A., Baskakov, O.I., Dyubko, S.F., 1997. Microwave spectrum of selenium dioxide. Proc. SPIE, 3090, pp. 163–166. DOI: https://doi.org/10.1117/12.26775631. King, G.W., Meatherall, R.C., 1984. Selenium dioxide: Analysis of the 419-nm absorption system. J. Mol. Spectrosc., 106(1), pp. 196–216. DOI: https://doi.org/10.1016/0022-2852(84)90093-632. Crowther, S.A., Brown, J.M., 2004. The 313 nm band system of SeO2. Part 1: vibrational structure. J. Mol. Spectrosc., 225(2), pp. 196–205. DOI: https://doi.org/10.1016/j.jms.2004.03.00533. Crowther, S.A., Brown, J.M., 2004. The 313 nm band system of SeO2. Part 2: rotational structure. J. Mol. Spectrosc., 225(2), pp. 206–221. DOI: https://doi.org/10.1016/j.jms.2004.03.00634. Baskakov, O.I., Moskienko, M.V., Dyubko, S.F., 1975. Investigation of the rotation spectra of HCOOH, DCOOH, HCOOD, and DCOOD in the submillimeter range. J. Appl. Spectrosc., 23(4), pp. 1377–1379. DOI: https://doi.org/10.1007/BF0061809035. Alekseev, E.A., Motiyenko, R.A., Margulès, L., 2012. Millimeter- and submillimeter-wave spectrometers on the basis of direct digital frequency synthesizers, Radio Phys. Radio Astron., 3(1), pp. 75–88. DOI: https://doi.org/10.1615/RadioPhysicsRadioAstronomy.v3.i1.10036. Alekseev, E.A., Ilyushin, V.V., Budnikov, V.V., Pogrebnyak, M.L., Kniazkov, L.B., 2023. Modernization of the Kharkiv microwave spectrometer: Current state. Radio Phys. Radio Astron., 28(3), pp. 257–270. DOI: https://doi.org/10.15407/rpra28.03.25737. Kirchhoff, W.H., 1972. On the calculation and interpretation of centrifugal distortion constants: A statistical basis for model testing: The calculation of the force field. J. Mol. Spectrosc., 41(2), pp. 333–380. DOI: https://doi.org/10.1016/0022-2852(72)90210-X38. Watson, J.K.G., 1967. Determination of centrifugal distortion coefficients of asymmetric‐top molecules. J. Chem. Phys., 46(5), pp. 1935–1949. DOI: https://doi.org/10.1063/1.1840957